Revision of Matsumuraja (Hemiptera, Aphidinae, Macrosiphini) in China with two new synonyms and four new records - Xu, Ying; Chen, Jing; Jiang, Liyun; Qiao, Gexia (Zootaxa, 2024)
The genus Matsumuraja Schumacher, 1921 is an eastern Asiatic genus and was reviewed in China. After this research, M. polydactylota Qiao & Zhang syn. nov. was regarded as the synonym of M. rubicola Takahashi; and Chaetosiphon anguifragum Zhang & Qiao syn. nov. was regarded as the synonym of M. rubifoliae Takahashi. Furthermore, M. rubi (Matsumura), M. rubiphila Takahashi, M. taisetsusana Miyazaki, M. urticae Ghosh, Ghosh & Raychaudhuri were first recorded in China. Seven species of the genus are now recognized in China. A key to species of Matsumuraja in China is presented.